Yishen Huashi Granules Ameliorated the Development of Diabetic Nephropathy by Reducing the Damage of Glomerular Filtration Barrier - Zhao, Tingting; Li, Minyi; Xiang, Qian; Lie, Beifeng; Chen, Deqi; Wang, Weiming; Li, Xuling; Xu, Tiancheng; Zhang, Xi; Li, Yuntong; Dong, Ruixue; Du, Xinwen; et al. (Frontiers in Pharmacology, 2022)
Background: Diabetic nephropathy (DN) is one of the most common complications of diabetes and the primary cause of end-stage renal disease. At present, renin–angiotensin–aldosterone system (RAAS) blockers have been applied as first-class drugs to restrain development of DN; however, its long-term effect is limited. Recent evidence has shown definite effects of Chinese medicine on DN. Yishen Huashi (YSHS) granule is a traditional Chinese Medicine prescription that has been used in the clinic to treat DN, but its mechanism is not understood. Methods: In the present study, both in vitro and in vivo studies were carried out. The DN model was induced by STZ in Wistar rats, and GEnC and HPC cell lines were applied in the in vitro study. Quality of YSHS was evaluated by LC-MS/MS. A metabolomic study of urine was carried out by LC-MS; influence of YSHS on composition of DN was analyzed by network pharmacology. Mechanism of the YSHS on DN was analyzed by Q-PCR, Western Blot, and multi-immunological methods. Results: We found YSHS administration significantly reduced levels of HbA1c and mALB. Histopathological analysis found that YSHS preserved integrity of glomerular filtration barrier by preserving viability of glomerular endothelial cells and podocytes, inhibiting glomerular fibrosis, reducing oxidative stress damage, and enhancing cross-talk among glomerular endothelial cells and podocytes. Network pharmacology, differential metabolite analysis, as well as intracellular pathway experimental study demonstrated that the PI3K/AKT/mTOR signaling pathway played a pivotal role in it. Conclusion: Our present findings supplied new understanding toward the mechanism of YSHS on inhibiting DN.